Ankle Foot Orthosis (AFO) stiffness design for mitigation of ankle inversion injury - Teixeira, D. (2020)
Modelling and simulation of human movement has the potential to improve the design of medical devices and rehabilitation process by enabling the identification of cause-effect relationships in individuals suffering from neurological and musculoskeletal issues. The main goal of this work was to provide a simulation-based stiffness design for an Ankle Foot Orthosis (AFO) that can help to mitigate the risk of a sprain by ankle inversion during the landing in freefall which is known to occur for subtalar angles higher than 25 degrees. Computational simulations were performed using human movement models with and without a passive AFO, to access the AFO sensitivity for the translational stiffness that prevents the cuff from translating with respect to the footplate. The Design of Experiments (DoE) methodology was used to access sensitivities between the three principal directions of the AFO stiffness. Results revealed that the ankle inversion angle was less than 25 degrees when increasingly larger values of translational stiffness were used, although a nonlinear behaviour was observed between the three principal directions of the AFO stiffness, for which injury safe design configurations were obtained.